Effect of Diluent Addition on Combustion Characteristics of Methane/Nitrous Oxide Inverse Tri-Coflow Diffusion Flames. Issue 10 (27th July 2022) - Li, Yueh-Heng; Chen, Chun-Han; Ilbas, Mustafa
ABSTRACT: The purpose of this study is to examine the dilution effect on combustion characteristics of methane/nitrous oxide inverse tri-coflow diffusion flame through the addition of various dilution gases. Two diluents, namely carbon dioxide and argon, were used. To scrutinize the overall combustion characteristics, the effects of dilution on flame appearance and pollution emissions were calculated numerically and observed experimentally. In terms of flame appearance, with increasing the central oxidizer flow rate, the flame became an inner-oxidizer-injected flame structure and then converted to a double flame structure. When 40% Ar and 20% CO2 were added to the oxidizer individually, a liftoff edge flame was formed at high central oxidizer flow rate. This theoretical prediction provided a fast and preliminary explanation of the various flame structures and concurred with the trend of IDF formation observed in the experiment. Regarding the flue gas emission, the addition of Ar in CH4 /N2 O diffusion flame can effectively reduce the yield of CO, whereas the addition of CO2 leads to an increase of CO concentration in the flue gas. Simulation results indicated that for Ar addition, the production of NOx is dominated by the inert effect at dilution levels lower than 40%, whereas the thermal/diffusion effect dominates at dilution levels higher than 40%. CO formation is mainly dominated by the thermal/diffusion effect. In CO2 dilution, NOx formation is dominated by the inert and chemical effects at dilution levels lower than 40%. However, at dilution levels higher than 40%, the chemical effect is more dominant. Thus, CO formation is dominated mainly by the chemical effect.